Information spillovers around seasoned equity offerings - Bradley, Daniel; Yuan, Xiaojing (Journal of Corporate Finance, 2013)
We examine information spillovers in the context of seasoned equity offerings (SEOs). Rival firms react significantly positively (0.26%) to primary SEO announcements, indicative of a competitive effect, but negatively (−0.35%) to secondary share announcements, which is evidence of a contagion effect. Consistent with the view that primary equity offerings signal favorable industry prospects because firms presumably issue new shares to invest in profitable projects, we find that the rival response is positively related to analysts' EPS growth forecasts. However, when insiders are selling their shares through a secondary offer, this may suggest overvaluation and thus negatively impacts rival firms. Consistent with this view, we find when VCs sell through a secondary offerings, rivals experience a more significant negative reaction. We find rival firms are more likely to follow their peers and conduct a primary SEO if the market reacts favorably to their peer's SEO announcement. Finally, rival firms outperform secondary share issuers of equity, but not primary share issuers. Collectively, the findings support the view that insiders take advantage of windows of opportunity when they sell their own shares, but not when they raise capital for investing purposes.